BRUNO’S INNER CONFLICT IN JOHN BOYNE’S THE BOY IN THE STRIPED PAJAMAS - ANSY KIRANA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
The Boy in the Stripped Pajamas written by John Boyne becomes one inspirational masterpiece in literature. The Boy in the Stripped Pajamas mainly talks about a journey of the main character to discover a secret in Out-With. The aim of the study is to analyze how Bruno as the main character characterized in this novel, describing the inner conflict that the main character faces in the novel. Inner conflict are used to conduct the analysis. In this inner conflict, Bruno broke to his Father orders do not leave the house in Berlin and even to go to visit who is behind the fence of his home which is also the prison of the Jews. Bruno never regretted his move to Auschwitz as being threatened because he has left all his best friends in Berlin and he got a new best friend in there. The various situation and various conflicts make up Bruno able to cope with them. He should be able to determine how to manage the inner conflict right in each of them. Thinking skills to put friendship above all, make him a child to bear a great risk for the sake of his friend. Keywords : inner conflict